2014
DOI: 10.1155/2014/249856
|View full text |Cite
|
Sign up to set email alerts
|

Worldwide Dissemination of the NDM-Type Carbapenemases in Gram-Negative Bacteria

Abstract: The emergence of one of the most recently described carbapenemases, namely, the New Delhi metallo-lactamase (NDM-1), constitutes a critical and growingly important medical issue. This resistance trait compromises the efficacy of almost all lactams (except aztreonam), including the last resort carbapenems. Therapeutical options may remain limited mostly to colistin, tigecycline, and fosfomycin. The main known reservoir of NDM producers is the Indian subcontinent whereas a secondary reservoir seems to have estab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
326
0
17

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 420 publications
(358 citation statements)
references
References 99 publications
15
326
0
17
Order By: Relevance
“…En Colombia estas dos enzimas son endémicas en Pseudomonas spp (26,27). Además, se detectó por primera vez la presencia de GES y un aislamiento portador de NDM, enzima que se considera poco frecuente en este microorganismo (28).…”
Section: Discussionunclassified
“…En Colombia estas dos enzimas son endémicas en Pseudomonas spp (26,27). Además, se detectó por primera vez la presencia de GES y un aislamiento portador de NDM, enzima que se considera poco frecuente en este microorganismo (28).…”
Section: Discussionunclassified
“…Overnight cultures grown at 37°C were diluted 1:100 in 5 mL LB with 5 μCi/mL 32 PO 4 and were grown at 37°C in a shaking water bath for 3 h. Lipid A abundance was analyzed with a mild acid-hydrolysis method (18,52). Briefly, 32 PO 4 -radiolabeled lipid A samples were dried under a stream of nitrogen gas.…”
Section: Methodsmentioning
confidence: 99%
“…82 Similar to E. coli isolates described above, NDMproducing K. pneumoniae and other enteric gram-negatives are extensively isolated from out-and in-patient settings and also from the environment in Indian subcontinent. 106 EARS-Net database in 2013 indicated that Greece (59.4%), Italy ( 34.3%) and Romania (20.5% ) have the highest rates of carbapenem resistance in K. pneumoniae. 17 The remaining countries in the EU have a prevalence <2%.…”
Section: Klebsiella Pneumoniaementioning
confidence: 99%
“…The majority of NDM-producing Acinetobacter spp are reported from China and the Middle-East. 106 Species identification may be important within the A. baumannii group since carbapenem resistance is more frequently reported in A. baumannii and mortality is much higher in patients with bacteremia casused by these strains as compared with other species such as A. pittii and A. nosocomialis which are the other clinically important members of the A. baumannii group. 114 Various carbapenemases including (NDM-type and Class D enzymes) are also described in A. pittii, recently.…”
Section: Acinetobacter Baumanniimentioning
confidence: 99%